Varieties of openness and types of digital anthropology: avoiding confusion in discussing Danny Miller - Zeitlyn, D; Lyon, S (2012)
Response to Miller's article in Hau 2012: http://www.haujournal.org/index.php/hau/article/view/93/114 about open access publishing in anthropology and various other topics such as linguistic hegemony and digital anthropology